Integration of GPS, GIS and remote sensing technology for landslide hazard analysis : a case study of western Himalayan Kaghan Valley, Pakistan - Akbar, Tahir Ali; Ha, Sung Ryong; Honda, Kiyoshi; Preeda Pakpian; Partial Scholarship, Asian Institute of Technology, ICIMOD (Bangkok : Asian Institute of Technology, 1998)
The purpose of this study is to integrate GPS, GIS & Remote Sensing Technology for making landslide hazard zonation map. A field survey is made with Global Positioning system (GPS) to locate the positions of landslides in the study area. From the coordinates obtained from GPS, a landslide map is prepared fo r the study area. Different factors like Aspect, drainage, elevation, geology, road construction, slope, isohyetal data, land cover and soil have been considered for the occurrence of landslides. By using GIS & Remote Sensing Technology landslide occurrences on all these factors have been analysed. The vector based GIS has been used for digitizing to produce thematic maps, as analysis for study was based on the pixel based information therefore Raster based GIS has been used for the anlysis. The contour map has been scanned, edited and elevation values are given to it to generate Digital Terrain Model (DTM) form it. Aspect, elevation and slope maps have been obtained form DTM.Land cover map has been produced from the Panchromatic SPOT data. Pixel based calculation was made by using the Information value Model. By using the information model we obtained the information values for all classes of all factor maps. On the basis of these information values all factor maps are recoded and matrix analysis was performed to produce a landslide hazard zonation map. The landslide hazard zonation map has been applied to digitize new road routes in the study area by avoiding high hazard area. Different factors have been considered for observing the most suitable road route.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Landslide hazard analysis -- Pakistan -- Kaghan Valley